Exceptional preservation of palaeozoic steroids in a diagenetic continuum - Melendez, Ines; Grice, Kliti; Schwark, Lorenz (Nature Publishing Group, 2013)
The occurrence of intact sterols has been restricted to immature Cretaceous (~125 Ma) sediments with one report from the Late Jurassic (~165 Ma). Here we report the oldest occurrence of intact sterols in a Crustacean fossil preserved for ca. 380 Ma within a Devonian concretion. The exceptional preservation of the biomass is attributed to microbially induced carbonate encapsulation, preventing full decomposition and transformation thus extending sterol occurrences in the geosphere by 250 Ma. A suite of diagenetic transformation products of sterols was also identified in the concretion, demonstrating the remarkable coexistence of biomolecules and geomolecules in the same sample. Most importantly the original biolipids were found to be the most abundant steroids in the sample. We attribute the coexistence of steroids in a diagenetic continuum-ranging from stenols to triaromatic steroids-to microbially mediated eogenetic processes.